Hechtia aquamarina, a new name for Hechtia pueblensis I. Ramírez & Jiménez - M., Ivón M. Ramírez; Nah, Carlos F. Jiménez (Phytotaxa, 2012)
The new name Hechtia aquamarina is proposed to replace Hechtia pueblensis I. Ramírez and Jiménez, a name blocked by H. pueblensis Burt-Utley, Utley & García-Mendoza.